Children Financial Education Using An Interactive Tool Addressing Multiple Learning Domains: A Case Study On Product Development Processes Of Muamalat Interactive Game - Zurina Shafii; Syahidawati Hj. Shahwan; Supiah Salleh; Norhazlina Ibrahim; Kasumalinda Alwi; Safeza Mohd Sapian; Halizah Md Arif (HIKARI Ltd, 2024)
Studies on financial education highlight the need for having children to be exposed on financial management to inculcate sense of responsibility on financial management. The challenge, however is to engage them with the concepts and the same time to deliver the content is engaging and fun manners. The purpose of this study is to highlight key activities involved in the product development of an interactive learning tool, Muamalat Interactive Game. Muamalat Interactive Game (MIG) is a game-based educational tool that i) exposes the players to Islamic banking, investment and social finance instruments ii) promotes inclusive economic development by inculcating the spirit of gift economy. Single case study analysis is adopted in this study on the processes involved for product development of a financial education board game; product conceptualisation, validation and pilot testing to intended users. Descriptive reporting on product conceptualisation and content as well as content and pedagogical validation are provided in the paper. For the pilot testing stage, the learning behaviours of learners are examined from the aspects of Cognitive Knowledge, Affective Behaviors and Technical Skills gained from the pilot testing conducted to the group of 70 secondary children. Learning behaviors of the learners relates to the cognitive ability to identify wealth management vehicles such as real property, share investment and Islamic insurance products as the players are to accumulate wealth using Shariah-compliant and ethical-based investment vehicles. The affective aspect of the learning is tackled from the engagement on charity-giving as the game instills the willingness to share personal wealth built-up over the rounds of game-playing to the Sadaqah house via donation (sadaqah) and endowment (waqf). Sadaqah house serves as the communal fund that restores widened economic gap. The players too, gain technical skills of managing personal finance such as planning and recording cash inflows and outflows, budgeting personal expenses, managing debts, calculate tithe (zakat) due, and finally ascertain net wealth. The findings of this case study could be benefit future innovators wanting to learn product development of serious games.